Birch pollen sensitization with cross‐reactivity to food allergens predominates in adults with eosinophilic esophagitis. Issue 11 (12th October 2013) - van Rhijn, B. D.; van Ree, R.; Versteeg, S. A.; Vlieg‐Boerstra, B. J.; Sprikkelman, A. B.; Terreehorst, I.; Smout, A. J. P. M.; Bredenoord, A. J.
Abstract: EoE patients show variable sensitization patterns to food and aeroallergens. The value of allergy testing in adult EoE patients is unclear. Component‐resolved diagnosis (CRD) may offer additional insights into sensitization patterns. The aim of this study was to characterize sensitization patterns in adult EoE patients using CRD. Serum from 76 patients (17 female), age 38.6 ± 1.5 years, was analyzed for reactivity to 112 different allergen components using an immuno‐solid‐phase allergen chip (ISAC). We observed any sensitization in 59 patients (78%), of which 54 patients were polysensitized. Aeroallergen sensitization, mostly against components of grass or tree pollen, or house dust mite, was observed in 74% of the patients. Birch pollen (rBet v 1) sensitization with cross‐reactivity to food allergen components was observed in 30 patients (39%). In conclusion, food sensitizations in EoE patients are mainly caused by cross‐reactivity to food allergens after primary birch pollen sensitization. Pollen and food sensitizations may cause or maintain esophageal inflammation in EoE patients. CRD provides more insight into sensitization patterns, identifies additional food allergen sensitizations and might be useful to direct dietary therapy in EoE.